A Geophysical Review of the Seabed Methane Seepage Features and Their Relationship with Gas Hydrate Systems. (12th October 2021) - Yang, Jinxiu; Lu, Mingyue; Yao, Zhiguang; Wang, Min; Lu, Shuangfang; Qi, Ning; Xia, Ying
Abstract : Seabed methane seepage has gained attention from all over the world in recent years as an important source of greenhouse gas emission, and gas hydrates are also regarded as a key factor affecting climate change or even global warming due to their shallow burial and poor stability. However, the relationship between seabed methane seepage and gas hydrate systems is not clear although they often coexist in continental margins. It is of significance to clarify their relationship and better understand the contribution of gas hydrate systems or the deeper hydrocarbon reservoirs for methane flux leaking to the seawater or even the atmosphere by natural seepages at the seabed. In this paper, a geophysical examination of the global seabed methane seepage events has been conducted, and nearby gas hydrate stability zone and relevant fluid migration pathways have been interpreted or modelled using seismic data, multibeam data, or underwater photos. Results show that seabed methane seepage sites are often manifested as methane flares, pockmarks, deep-water corals, authigenic carbonates, and gas hydrate pingoes at the seabed, most of which are closely related to vertical fluid migration structures like faults, gas chimneys, mud volcanoes, and unconformity surfaces or are located in the landward limit of gas hydrate stability zone (LLGHSZ) where hydrate dissociation may have released a great volume of methane. Based on a comprehensive analysis of these features, three major types of seabed methane seepage are classified according to their spatial relationship with the location of LLGHSZ, deeper than the LLGHSZ (A), around the LLGHSZ (B), and shallower than LLGHSZ (C). These three seabed methane seepage types can be further divided into five subtypes considering whether the gas source of seabed methane seepage is from the gas hydrate systems or not. We propose subtype B2 represents the most important seabed methane seepage type due to the high density of seepage sites and large volume of released methane from massive focused vigorous methane seepage sites around the LLGHSZ. Based on the classification result of this research, more measures should be taken for subtype B2 seabed methane seepage to predict or even prevent ocean warming or climate change.